PENGARUH MUKA AIR TANAH TERHADAP KESTABILAN JEMBATAN MENGGUNAKAN METODE ELECTRICAL RESISTIVITY TOMOGRAPHY KONFIGURASI DIPOLE-DIPOLE - Santoso, Budy; Setianto, Setianto; Wijatmoko, Bambang; Supriyana, Eddy (PROSIDING SEMINAR NASIONAL FISIKA (E-JOURNAL), 2017)
Ground water is one of the factors that affect the stability of a bridge. One of the Geophysical Methods that can identify the presence of groundwater is Electrical Resistivity Tomography (ERT) method. Configuration of ERT measurement using Dipole-Dipole Configuration. Based on ERT measurements that have been correlated with local geology, the following results are obtained: porous pile soil has a resistivity value : (42 - 58) Ohm.m, below the porous layer there is a water table with resistivity value: (24 - 30) Ohm.m at depth : (6 - 10) m, and the lowest layer is a impermeable layer suspected of Claystone with resistivity value : (40 - 100) Ohm.m. This claystone is impermeable, consequently the groundwater that is in the layer will flow at lower altitude by bringing the material in the form of soil / rock that is covered by the coating, so that the soil / rock under the bridge becomes unstable. Keywords: groundwater, dipole-dipole, ERT, resistivity